Clinical Spectrum of Ocular and Visual Dysfunction in Children with Periventricular Leukomalacia: A Need for an Interdisciplinary Approach - Ozturker, Zeynep Kayaarasi; Bayar, Sezin Akca; Oto, Sibel; Aksoy, Sibel; Akkoyun, Imren; Sezer, Taner (Journal of Pediatric Neurology, 2021)
The study aimed to evaluate the ocular motility and visual and optic disc abnormalities in children diagnosed with periventricular leukomalacia (PVL). A retrospective analysis was performed on 51 consecutive children who had ophthalmic symptoms and were diagnosed with PVL by using magnetic resonance imaging. The patients were assessed for visual function, strabismus, cycloplegic refraction, fundus examination, and if appropriate, spectral-domain optical coherence tomography and visual field testing were applied. The primary outcome measures were the prevalence and visual and ocular motility dysfunctions. Mean age was 5.72 ± 2.6 years (range = 1–12), median birth weight was 2,740 g (range = 1,240–3,460), and median gestational age was 34 weeks (range = 28–38). In total, 21 patients (39.6%) had neurological deficit, 11 (21.5%) had intellectual disability, and 19 (37.2%) had no neurological symptom. In the spherical equivalent refractive error and cylinder power analysis, 10 patients had ≥3.0 D myopia, 15 had ≥3.0 D hyperopia, and eight had ≥2.50 D astigmatism. Thirteen (25.4%) children had a best-corrected visual acuity between 20/40 and 20/20 for Snellen card, while 9 (17.6%) had strabismic amblyopia and 6 (11.7%) had anisometropic amblyopia. Manifest strabismus was present in 35 patients (68.6%); of whom 12 had esotropia (23.5%), 16 had exotropia (31.3%) and 6 had vertical deviation (11.7%). Manifest or latent nystagmus was detected in 14 patients (27.4%). In 28 patients (54.9%), there was optic nerve abnormality. Two patients had hypoplastic disc, 14 had optic disc pallor, 7 had large cupping, and 5 had total optic atrophy. Six subjects underwent reliable visual field (VF) examinations, and all six had abnormal VFs, with inferior fields being most affected. Ocular motility disorders, optic nerve abnormalities, VF defects, and low visual acuity are common findings in this cohort of PVL patients and maybe the only presenting signs of the disease. The recognition of the visual disabilities and implementation of early rehabilitation may have a significant benefit in these children.
Keywords: periventricular leukomalacia; ocular motility; visual acuity; optic nerve; visual field